Public Relations Campaign Management for Supporting Responsible and Sustainable Tourism - Melati Andria Widanarko; Gayatri Atmadi (Ikatan Sarjana Komunikasi Indonesia, 2023)
Local community in Thousand Islands should know how to manage public relations campaign properly for supporting responsible and sustainable tourism. This research aims to know how Jejak Seribu can involve youth community in Tidung Island in managing public relations campaign for education exploration : Jelajah Edukasi : Entrepreneur Millenials 2019. This study uses qualitative-descriptive research approach with case study. The method of data collection in this study is in-depth interviews with the head of Jejak Seribu, the head of entrepreneurship division of Jejak Seribu, and members of Jejak Seribu. The results of this study show that Jejak Seribu has implemented the stages of campaign management in conducting the Entrepreneur Millennials campaign, and the application of the concept of responsible tourism, sustainable tourism and public relations campaign proves more effective in achieving campaign objectives.This research only focused on the very specific program of